The influence of selenium on thyroid gland - Szafraniec-Porada, Aneta; Porada, Dominik; Konopelko, Michał; Przybylska, Daria; Pucułek, Małgorzata (Journal of Education, Health and Sport, 2018)
The proper functioning of the thyroid gland depends on many factors, which include adequate supply of various trace elements, including iodine, but also selenium or iron. The purpose of this article was to attempt to summarize the current knowledge on the effects of selenium on the thyroid gland and the clinical implications associated with it.Selenium affects the homeostasis of the entire human body, and its main function in the thyroid gland is to counteract damage of oxidative origin. This microelement is part of selenoproteins, which include glutathione peroxidase and thioredoxin reductase. Both selenium deficiency and excess can negatively affect the thyroid gland. The research results show that selenium supplementation may bring benefits in some morbidities, eg Graves-Basedow disease. Currently, I advise recommending semi-annual selenium supplementation in a mild form of thyroid orbitopathy. However, no clinical benefit has been demonstrated in increasing the supply of selenium in the diet of other patients with thyroid disease, including Hashimoto's disease. In conclusion, despite the numerous studies already conducted, further work is necessary to fully explain the mechanisms of action of this element on the thyroid gland, but also to deepen knowledge about the benefits and risks of selenium supplementation in various types of thyroid structural disorders and, most importantly, to establish safe guidelines for possible treatment.